Competências do bibliotecário gestor como ferramentas estratégicas de auxílio à competitividade empresarial - Torres, Názia Holanda (2014)
Contemporary society deals with the challenge of managing a significant amount of information which is necessary to carry out the activities of citizens in their daily and professional life. Thus, companies deal with the challenge of managing their growing information flow, which starts with data collection and proceeds to the dissemination. From this perspective, this paper aims to analyze the skills of the managing librarian as strategic tools to aid business competitiveness, especially in Brazil's Micro and Small Business Support Service - Ceará (Sebrae - CE) Metropolitan Regional branch. Thereafter, operational goals are: (1) identifying the activities carried out by the librarian in the business information management process in that context; (2) identifying the skills and competences of the librarian in information management; (3) analyzing the contribution of the librarian as information manager for business competitiveness by making information available to the institution's clients. In order to achieve the aforementioned goals, theoretically, we studied the fundamental items for understanding the reality considered, such as conceptualization/evolution, intertwinements and interdisciplinarity existing between library science, documentation and information science. Additionally, the study includes information management (IM) intrinsic aspects, such as the distinction between data, information and knowledge and information management processes. Discussion on the competencies of the librarian in business information management is also explored. That requires an analysis of IM referred to by authors like Beuren (2000), Choo (2006), Davenport (1998), McGee and Prusak (1994). The importance of IM and knowledge management (KM) presented by Barbosa (2008) and Valentine (2004), and information management as a component of competitiveness, according to Silva (2001), is also emphasized. Methodologically, the research is qualitative and quantitative, having exploratory nature. It is a case study on SEBRAE - CE Metropolitan Regional branch. The research used interviews and questionnaires with librarians and external users (entrepreneurs and aspiring entrepreneurs) of the Center for Documentation and Information (CDI), respectively. Given the particularities and characteristics of the population, simple (probabilistic) random sampling process was adopted, whereas the selection of respondents is based upon a convenience sample (non-probabilistic). We draw on content analysis of the data collected in the search for answers to the objectives. From the research it may be inferred that the librarian's activities in the IM process consists in the identification of information needs, acquisition, organization, storage, distribution, and dissemination process. It is noteworthy that the librarian, throughout his/her formation and training, acquires skills and competencies that enable him/her to deal with information management. In addition, the librarian contributes significantly to business competitiveness by providing information, because it is consensual that users recognize the importance of the librarian in the IM process.